Pengaruh Literasi Keuangan Terhadap Kinerja Dan Keberlangsungan UMKM Di Kota Surabaya - Madaniyah Nur Aisyah Putri; Hwihanus Hwihanus (Master Manajemen, 2024)
This research uses MSMEs as objects engaged in wholesale and retail trade; Car and Motorbike Repair in Surabaya. This research aims to find out how financial literacy impacts the performance and continuity of research. This research was conducted through a questionnaire. The data analysis method used is Partial Least Square (PLS). The research results show that financial literacy influences the financial performance of MSMEs in Surabaya, and financial literacy variables influence the sustainability of their business.